Morphological Identification and Characterization of Pathogenic Fungi Associated with Imported and Local Fruits and Vegetables from Selected Retail Outlets in Tripoli, Libya - عفاف الصويعي; صفية البدوي; عالية دوزان; يوسف عزو (African Journal of Advanced Pure and Applied Sciences, 2026)
This study aimed to isolate and identify pathogenic fungi associated with imported and local fruits and vegetables from retail markets in Tripoli. A total of 52 samples—including mango, orange, lemon, and tomato (both imported and local)—were collected and cultured on Potato Dextrose Agar (PDA), yielding 510 fungal isolates identified at both genus and species levels. The dominant genera included Aspergillus, Mucor, Rhizopus, Saccharomyces, and Penicillium. Mucor sp. was most frequent in imported mangoes (49.3%), Saccharomyces sp. predominated in Abu-Sitta mangoes (45.6%), and Rhizopus sp. dominated in local mangoes (33%). Saccharomyces sp. was also prevalent in both imported and local oranges, while Mucor, Saccharomyces, and A. flavus were recurrent in lemon and tomato samples. The findings highlight the widespread presence of postharvest fungal contaminants in Tripoli’s produce markets and underscore the need for improved sanitation, storage, and handling practices to reduce fungal spoilage and safeguard consumer health.